Portuguese Tourism Demand: A Dynamic Panel Data Analysis - Leitão, Nuno Carlos (International Journal of Economics and Financial Issues, 2015)
This article considers the determinants of Portuguese tourism demand for the period 2004-2013. The econometric methodology uses a panel unit root test and the dynamic panel data (GMM-system estimator). The different techniques of panel unit root (Levin, Lin and Chu & Im, Pesaran and Shin W-stat & ADF - Fisher Chi-square) show that the variables used in this panel are stationary. The dynamic model proves that tourism demand is a dynamic process. The variables relative prices, income per capita, human capital and government spending encourage international tourism demand for Portugal Keywords: Tourism demand, dynamic panel data, panel unit root test, Portugal. JEL Classifications: C33; F10; H62